Transference effect of vertical and horizontal plyometrics on sprint performance of high-level U-20 soccer players - Loturco, I.; Pereira, L. A.; Kobal, R.; Zanetti, V.; Kitamura, K.; Cavinato Cal Abad, C.; Nakamura, F. Y. (Journal of Sports Sciences, 2015)
The aim of this study was to investigate the effects of adding vertical/horizontal plyometrics to the soccer training routine on jumping and sprinting performance in U-20 soccer players. The vertical jumping group (VJG) performed countermovement jumps (CMJ), while the horizontal jumping group (HJG) executed horizontal jumps (HJ). Training interventions comprised 11 sessions, with volume varying between 32 and 60 jumps per session. The analysis of covariance revealed that CMJ height and peak force improved only in the VJG, and that HJ distance and peak force improved in both groups. Velocity in 20 m (VEL 20 m) did not improve in either group; however, velocity in 10 m (VEL 10 m) presented a moderate positive effect size (ES = 0.66) in the HJG, while the ES was large (1.63) for improvement in the 10-20 m acceleration in the VJG, and it was largely negative (-1.09) in the HJG. The transference effect coefficients (calculated by the equation: TEC = result gain (ES) in untrained exercise/result gain (ES) in trained exercise) between CMJ and VEL 20 m and ACC 10-20 m were 1.31 and 2.75, respectively. The TEC between HJ and VEL 10 m, VEL 20 m and ACC 0-10 m were 0.44, 0.17 and 0.44, respectively. The results presented herein indicate that the plyometric training-axis is decisive in determining neuromechanical training responses in high-level soccer players.